The Long Winter - Wilder, Laura Ingalls; Nang ChanYeema (New York, USA Avon Books, 2003)
The town of De Smet faces a hard winter with dwindling food supplies. Can Almanzo Wilder succeed in finding wheat?
Keywords: Juvenile Fiction